2013
DOI: 10.1038/ejcn.2013.149
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient intake in the GEICO multicenter trial: the effects of a multicomponent worksite intervention

Abstract: Background/objectives:To assess the effects on macro- and micronutrient intake of a nutrition intervention program in corporate settings across the United States.Subjects/methods:Two hundred and ninety-two individuals who were overweight or had type 2 diabetes were recruited from 10 sites of a US insurance company. Two hundred and seventy-one participants completed baseline diet recalls, and 183 participants completed dietary recalls at 18 weeks. Sites were randomly assigned to an intervention group (five site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Iron intake was low among all groups. Both observational [2,3,46] and intervention studies [47][48][49] have shown higher or similar iron intakes between vegetarians and vegans as compared with omnivores, with the difference being that veg and vegan diets only contain nonheme iron. With the exception of an increase in potassium at 2 months among the vegan group, recommendations to follow any of the diets did not differentially impact potassium intake.…”
Section: Discussionmentioning
confidence: 94%
“…Iron intake was low among all groups. Both observational [2,3,46] and intervention studies [47][48][49] have shown higher or similar iron intakes between vegetarians and vegans as compared with omnivores, with the difference being that veg and vegan diets only contain nonheme iron. With the exception of an increase in potassium at 2 months among the vegan group, recommendations to follow any of the diets did not differentially impact potassium intake.…”
Section: Discussionmentioning
confidence: 94%
“…Clinical: to hypertension cohort--blood pressure; to hyperlipidemia cohort-HDL, LDL, Triglyceride; to diabetes cohort--HbA1c.2011Terry [41]Health2Baseline & postinterventionValidated Health Risk Assessment, established previously based on associations between assessed health risks & cardiac-associated mortality rates2012Lahiri [42]Work3Baseline, 16 wk, & 28 wk (absenteeism & presentism were only measured at baseline & wk 28)Absenteeism, Presentism by Work Limitations Questionnaires2012Malarkey [43]Health4Baseline, 2 mo, 6 mo, & 12 moBlood pressure, pulse rate, BMI, blood sample; Biomarkers: level of inflammatory peptide C-reactive protein, interleukin 6, salivary cortisol, leptin. Questionnaires: Perceived Stress Scale, Sleep-Pittsburgh Sleep Quality Index, depressive symptoms: Center for Epidemiological Studies Depression; mindfulness: The Toronto Mindfulness Scale2013Batra [44]Health2Baseline & postinterventionWeight; Food craving questionnaire, Three-factor eating questionnaire2013Salinardi [45]Health2Baseline & postintervention (weight was measured 6 times in intervention group during the 6 mo)Weight, height, blood pressure, blood glucose, total cholesterol & triglycerides2013Carr [46]Health2Baseline & postinterventionSedentary time measured by StepWatch physical activity monitor, blood pressure, body mass, heart rate, waist circumference, fasting blood lipids, estimated aerobic fitness2013Koepp [47]Work & health3Baseline, 6 mo, & 12 moDaily physical activity (using accelerometers), work performance, body composition, & blood variables: glucose, insulin, hemoglobin A1C, & lipids2013Kullgren [48]Health3Baseline, 24 wk, & 36 wk (weight was measured monthly during the 36 wk)Weight; Physical Activity Questionnaire, Three-Factor Eating Questionnaire-R18, participation in weight-related wellness programs2013Mishra [15]Health2Baseline & postinterventionOnline automated self-administered 24-h diet recall2014Carpenter [49]Health3Baseline, 6 mo, & 1...…”
Section: Resultsmentioning
confidence: 99%
“…The World Health Organisation defined a healthy workplace as "one in which workers and managers collaborate to use a continual improvement process to protect and promote the health, safety and well-being of all workers and the sustainability of the workplace" [4]. Employers are considered to be in a suitable position to help support and promote employee health and wellbeing in several areas including nutrition, physical activity, disease management and workplace environmental changes [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%